2013
DOI: 10.1016/j.molonc.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a microRNA‐based diagnostic assay for classification of renal cell carcinomas

Abstract: A B S T R A C TRenal cancers account for more than 3% of adult malignancies and cause more than 13,000 deaths per year in the US alone. The four most common types of kidney tumors include the malignant renal cell carcinomas; clear cell, papillary, chromophobe and the benign oncocytoma. These histological subtypes vary in their clinical course and prognosis, and different clinical strategies have been developed for their management. In some kidney tumor cases it can be very difficult for the pathologist to dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These molecules can differentiate ccRCC from papillary and chromophobe histologies (5) and have been associated with RCC metastasis (6)(7)(8) and aggressiveness (9)(10)(11)(12)(13)(14)(15). The Cancer Genome Atlas (TCGA) project on ccRCC showed that unsupervised analysis of miRNA expression can classify tumors into 4 distinct clusters of different survival, with miR-21 showing the strongest correlation with poor overall survival (OS) (9).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules can differentiate ccRCC from papillary and chromophobe histologies (5) and have been associated with RCC metastasis (6)(7)(8) and aggressiveness (9)(10)(11)(12)(13)(14)(15). The Cancer Genome Atlas (TCGA) project on ccRCC showed that unsupervised analysis of miRNA expression can classify tumors into 4 distinct clusters of different survival, with miR-21 showing the strongest correlation with poor overall survival (OS) (9).…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing discussion and also already initiated clinical trials (‘basket' and ‘umbrella' clinical trial design) that aim on histology-independent and aberration-specific clinical trials ( Menis et al , 2014 ). The ability to classify histological subtypes by microRNA-based assays has also been successfully demonstrated for kidney cancer, pleura mesothelioma and other types of cancer ( Benjamin et al , 2010 ; Spector et al , 2013 ).…”
Section: Micrornas In Cancer Diagnosismentioning
confidence: 99%
“…36 A handful of miRNA-based tests aimed at guiding therapeutic management have been already approved by FDA for applications such as classification of cancer of unknown primary origin (CUP), lung cancer type classification, thyroid cancer stratification, and breast cancer metastasis and recurrence analysis, based on the differential expression of miRNA biomarker sets. [37][38][39][40][41][42][43][44][45] Unlike the tests for viral RNA, which are offered as kits with a companion platform, cancer testing is offered as a service to healthcare providers. Most studies so far have dealt measuring the concordance of test results with immunohistochemistry and pathology in cancer typing and stratification.…”
Section: Fda-approved Rna Assays and Platformsmentioning
confidence: 99%